(untitled) (Iranian Journal of Kidney Diseases, 2015)
Fabry disease, an X-linked lysosomal storage disorder, is caused by α-galactosidase A deficiency and leads to accumulation of glycospinhgolipids in most tissues, with life-theratening consequences in the kidney, heart, and cerebrovascular system. Enzyme replacement therapy is available as 2 different preparations: agalsidase alfa and agalsidase beta. Enzyme replacement therapy is started as soon as the diagnosis is confirmed, but there is no data available in the literature about its safety during preganacy. Herein, we described 2 patients with Fabry disease who received agalsidase beta during their pregnancy. This report is important as the data about enzyme replacement therapy during pregnancy is restricted with case reports.